RAMBUTAN HONEY PHARMACEUTICAL STANDARDIZATION FOR WOUND HEALING TREATMENT - Euis Reni Yuslianti; Boy Muclish Bachtiar; Dewi Fatma Suniarti; Afifah Bambang Sutjiatmo (Bionatura, 2018)
Human wounds require proper management so they may heal faster and without complication. Honey is empirically effective to accelerate wound healing but scientifically has been proven yet as a pharmaceutical product is very limited. This study aimed to obtain rambutan honey pharmaceutical grade by setting specific and nonspecific parameters of simplicia. The research method was experiments laboratory by nonspecific parameters test (diastase enzyme activity, HMF, pH value, moisture content, ash content, glucose level, heavy metal contamination: Pb, Cd, Hg, and As, chloramphenicol, microbial contamination: coliform, and yeasts) as well as specific parameters (simplicia identity and organoleptic test). The results showed that rambutan honey proved had good quality of specific and nonspecific parameters. Rambutan honey water content has been pharmaceutical standardized according to drug standard that is to be 10.15%. Based on the results of this study it is necessary to test rambutan honey efficacy in vivo and in vitro and effects of rambutan honey topical products to humans towards phytopharmaca medicine.